2022
DOI: 10.3389/fnagi.2022.795132
|View full text |Cite
|
Sign up to set email alerts
|

The Aged Striatum: Evidence of Molecular and Structural Changes Using a Longitudinal Multimodal Approach in Mice

Abstract: To study the aging human brain requires significant resources and time. Thus, mice models of aging can provide insight into changes in brain biological functions at a fraction of the time when compared to humans. This study aims to explore changes in dopamine D1 and D2 receptor availability and of gray matter density in striatum during aging in mice and to evaluate whether longitudinal imaging in mice may serve as a model for normal brain aging to complement cross-sectional research in humans. Mice underwent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 53 publications
(65 reference statements)
1
7
0
Order By: Relevance
“…Several studies have demonstrated the significance of DA signalling in the maintenance of motor function, and that declines in dopamine functional component availability might be responsible for age-related behavioural deficits [50][51][52][53][54]. In the treated group, the gene expression of DA markers demonstrated an overall increase compared to that in aged rats.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Several studies have demonstrated the significance of DA signalling in the maintenance of motor function, and that declines in dopamine functional component availability might be responsible for age-related behavioural deficits [50][51][52][53][54]. In the treated group, the gene expression of DA markers demonstrated an overall increase compared to that in aged rats.…”
Section: Discussionmentioning
confidence: 97%
“…The impact of age on several DA targets, including receptors, transporters, and relevant enzymes in the striatum, has been reported [50][51][52][53][54]. Gene expression of the main functional components of DA neurones was assessed in the different groups.…”
Section: Bmmscs Restored Da System Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most significant observations from these novel experiments is the shift in motivation between 6- and 12-months of age in both C- and HF-fed offspring. Aging is associated with reduced food cravings in humans [ 62 ] and decreased motivation and reduced striatal D2R availability in male C57Bl/6 mice [ 63 , 64 , 65 , 66 ]. Thus, the shift towards decreased motivation in the 12-month-old C/C male mice is consistent with a natural age-related decline.…”
Section: Discussionmentioning
confidence: 99%
“…The three cohorts underwent functional and structural MRI in three batches. Males of the first ( n = 9) and third ( n = 8) cohorts also underwent PET/CT experiments 48 . A summary of all animals and their functional MRI sessions (12-24 motnhs) are listed in Supplementary Data 2 .…”
Section: Methodsmentioning
confidence: 99%